Cross-Border Private Equity Syndication: The Effect of Institutional Environment and Organisation Learning - Chopraa, Riya (2008)
Private Equity (PE) is a progressive international phenomenon. However, the research in this field lacks the investigation of the factors that influence the private equity firms' investment decisions when investing across the national borders. The novel aspect of this research is that it aims to fill the gap in the cross-border syndication literature by the examining the affect of the institutional factors and organisational learning on a private equity firms' cross-border syndication decisions.